2019
DOI: 10.1096/fj.201901345r
|View full text |Cite
|
Sign up to set email alerts
|

Time‐course of sodium transport along the nephron in nephrotic syndrome: The role of potassium

Abstract: The mechanism of sodium retention and its location in kidney tubules may vary with time in nephrotic syndrome (NS). We studied the mechanisms of sodium retention in transgenic POD-ATTAC mice, which display an inducible podocyte-specific apoptosis. At day 2 after the induction of NS, the increased abundance of NHE3 and phosphorylated NCC in nephrotic mice compared with controls suggest that early sodium retention occurs mainly in the proximal and distal tubules. At day 3, the abundance of NHE3 normalized, phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 42 publications
(79 reference statements)
3
16
0
3
Order By: Relevance
“…Increased albuminuria was equivalent across mouse strains, however, in the 7 days following glomerular injury (Figure 2j ). The proteinuric time course was thus similar to previous studies using this model (Dizin et al, 2020 ; Rutkowski et al, 2013 ). The dimerizer agent utilized to induce the caspase‐8 mediated podocyte apoptosis caused no functional effects in wild‐type mice (Figure S1a–f ).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Increased albuminuria was equivalent across mouse strains, however, in the 7 days following glomerular injury (Figure 2j ). The proteinuric time course was thus similar to previous studies using this model (Dizin et al, 2020 ; Rutkowski et al, 2013 ). The dimerizer agent utilized to induce the caspase‐8 mediated podocyte apoptosis caused no functional effects in wild‐type mice (Figure S1a–f ).…”
Section: Resultssupporting
confidence: 86%
“…Another study further supports a beneficial role for intrarenal CD4+ T cell presence and reported that infusion of CD4+CD25+ Tregs at day 1 post‐IRI had a protective role by modulating pro‐inflammatory cytokines (Gandolfo et al, 2009 ). Our study utilized the POD‐ATTAC model, which has been previously reported as a model of focal segmental glomerulosclerosis (FSGS), otherwise known as nephrotic syndrome (Dizin et al, 2020 ; Rutkowski et al, 2013 ). The use of this model provides a genetic tool to investigate progressive renal disease initiated from a one‐time isolated glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dans ce modèle, le syndrome néphrotique est provoqué par une apoptose inductible des podocytes glomérulaires [37]. Dans ce modèle de syndrome néphrotique, l'étude de la cinétique de la rétention sodée permet d'identifier deux phases : une première phase, pendant laquelle la réabsorption excessive de sodium a lieu dans le tube contourné distal via une activation de NCC ; et une seconde phase, dans laquelle la rétention sodée se situe au niveau du système collecteur via une activation de ENaC [38]. Ce changement de site de rétention sodée est lié à l'apparition d'une hyperkaliémie.…”
Section: Apport Des Modèles Expérimentaux Murins Pour La Physiopathol...unclassified